FACTORS OF CONSUMER BEHAVIOR IN A VISIT TO CAMPOENG KOPI RIGIS JAYA: FAKTOR PERILAKU KONSUMEN DALAM BERKUNJUNG KE KAMPOENG KOPI RIGIS JAYA - Widisono, Rachmawati Lola; Ali, Suprihatin; Subagja, Ghia (Jurnal Kompetitif Bisnis, 2023)
This research explains consumer behavior factors that show various tendencies in visiting Kampoeng Kopi Rigis Jaya. The data in this research is primary data taken using a questionnaire. The sample in this study amounted to 100 samples taken using purposive sampling technique. This type of research is quantitative research and the sampling technique uses purposive sampling with a non-probability sampling method with a sample size of 100 respondents. Data was obtained from a questionnaire using the Method of Successive Interval (MSI). This research data analysis uses multiple linear regression analysis with simultaneous results. The Visit Decision Factor variable has a significant effect on purchasing decisions at Kampoeng Kopi Rigis Jaya with an R Square value of 0.357 or 35%. Meanwhile, partial results show that many consumers visit Kampoeng Kopi because of cultural factors, personal factors and psychological factors.